COMMERCIAL-FREE TV?: EXAMINING THE COMMODITY FLOW OF NETFLIX - Yale, Camille (AoIR Selected Papers of Internet Research, 2015)
Television is changing, or so we’re told. People are recording programs and watching them when they want, they’re skipping ads, they’re cutting the cable cord, they’re binge viewing, they’re mobile viewing, they’re multi-screening. It’s all up for grabs. Netflix is a player in this TV revolution, and its rallying cry is its modest price and personalized, commercial-free experience. It is true that unlike YouTube and Hulu, Netflix does not require its users to view traditional commercials before streaming videos on their platform. But is it fair to say that Netflix is a commercial-free service, separated from the practices and constructs of marketing and consumer culture? In this paper I take on the assertion that Internet media services like Netflix are challenging the commercially-driven traditional media model and democratizing media consumption. Through McAllister & Giglio’s (2004) work on the “commodity flow” of television and Andrejevic’s thesis on the “work of being watched,” I argue that Netflix and other online streaming services represent a rearticulation of the traditional media system, including an intense commodity orientation and oligopolistic market practices.